The Dawning Era of Comprehensive Transcriptome Analysis in Cellular Microbiology - Aikawa, Chihiro; Maruyama, Fumito; Nakagawa, Ichiro (Frontiers in Microbiology, 2010)
Bacteria rapidly change their transcriptional patterns during infection in order to adapt to the host environment. To investigate host-bacteria interactions, various strategies including the use of animal infection models, in vitro assay systems and microscopic observations have been used. However, these studies primarily focused on a few specific genes and molecules in bacteria. High-density tiling arrays and massively parallel sequencing analyses are rapidly improving our understanding of the complex host-bacterial interactions through identification and characterization of bacterial transcriptomes. Information resulting from these high-throughput techniques will continue to provide novel information on the complexity, plasticity and regulation of bacterial transcriptomes as well as their adaptive responses relative to pathogenecity. Here we summarize recent studies using these new technologies and discuss the utility of transcriptome analysis.